2022
DOI: 10.14814/phy2.15543
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 4 weeks of western diet and aerobic exercise training on whole‐body phenotype and skeletal muscle mitochondrial respiration in male and female mice

Abstract: High dietary fat intake induces significant whole-body and skeletal muscle adaptations in mice, including increased capacity for fat oxidation and mitochondrial biogenesis. The impact of a diet that is high in fat and simple sugars (i.e., western diet [WD]), particularly on regulation of skeletal muscle mitochondrial function, is less understood. The purpose of the current study was to determine physiologic adaptations in mitochondrial respiratory capacity in skeletal muscle during short-term consumption of WD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…In the current study, there were several differential outcomes in males and females. Females, for example, demonstrated some compensatory WD adaptations (e.g., absolute muscle mass), which is consistent with previous studies reporting female protection against high‐fat diet‐derived obesity 30,35 . To date, numerous studies have revealed that females have greater mitochondrial content and mitochondrial biogenesis‐related gene responses compared to males; notably, quantifying sex differences was outside the statistical model for our study 36,37 .…”
Section: Discussionsupporting
confidence: 90%
“…In the current study, there were several differential outcomes in males and females. Females, for example, demonstrated some compensatory WD adaptations (e.g., absolute muscle mass), which is consistent with previous studies reporting female protection against high‐fat diet‐derived obesity 30,35 . To date, numerous studies have revealed that females have greater mitochondrial content and mitochondrial biogenesis‐related gene responses compared to males; notably, quantifying sex differences was outside the statistical model for our study 36,37 .…”
Section: Discussionsupporting
confidence: 90%
“…but not female mice (Ehrlicher et al, 2020;McGowan et al, 2022). The females in our current training protocol improved performance during graded exercise tests, yet it is possible that lower absolute work in females or lack of robust training stimulus may contribute to why there were no major changes in glucose homeostasis nor body composition.…”
Section: Pdhbmentioning
confidence: 81%
“…Our purpose was to investigate ETF abundance and turnover in female mice as a mechanism contributing to changes in mitochondrial fat oxidation to HFD and exercise. HFD increases lipid respiration in males (Ehrlicher et al., 2020), which often have lower respiration than females (Cardinale et al., 2018; McGowan et al., 2022; Miotto et al., 2018; Montero et al., 2018). We studied female mice to determine if lipid respiration can be further stimulated amidst a background of higher intrinsic lipid respiration.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations